Culture, tradition, and taboo: understanding the social shaping of fuel choices and cooking practices in Nigeria - Akintan, Oluwakemi; Jewitt, Sarah; Clifford, M.J. (Elsevier, 2018)
Wood fuel remains the most widely used domestic fuel amongst resource poor groups in many low-income countries, despite the environmental and health problems associated with exposure to wood smoke. Studies on household air pollution concentrate predominately on socio-economic and behavioural factors and health with little emphasis on socio-cultural factors. The study contributes to the understanding of household air pollution (HAP) and wood fuel harvesting for domestic activities in low-income countries from a cultural perspective that draws on householders’ wood fuel selection and cooking practices in Ado Ekiti, Nigeria. In this paper, we explore how cultural norms influence households’ cooking practices, energy choices and perceptions of the causes of ill health and misfortune. The research draws on household surveys, participant observation and semi-structured interviews with householders of four different ethnic origins in nineteen villages. Key findings reveal low levels of awareness of HAP-related illness coupled with high levels of attachment to traditional biomass-fuelled cooking systems for a range of cultural and pragmatic reasons. It is argued that ‘ethnic-specific’ traditional norms and taboos provide a more important influence on fuel choice, wood fuel harvesting and cooking practices than the lived realities of exposure to household air pollution.